2016
DOI: 10.2215/cjn.04230415
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Urinary Uromodulin with Clinical Characteristics and Markers of Tubular Function in the General Population

Abstract: Background and objectives Allelic variants in UMOD, the gene coding for uromodulin, are associated with rare tubulointerstitial kidney disorders and risk of CKD and hypertension in the general population. The factors associated with uromodulin excretion in the normal population remain largely unknown, and were therefore explored in this study.Design, setting, participants, & measurements Urinary uromodulin excretion was measured using a validated ELISA in two population-based cohorts that included more than 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
103
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 35 publications
6
103
2
1
Order By: Relevance
“…Notably, THP level in urine appears to be a valuable indicator of functional kidney mass and the respective UMOD gene is associated with chronic kidney disease and, especially, diabetic kidney damage by mechanisms to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, THP level in urine appears to be a valuable indicator of functional kidney mass and the respective UMOD gene is associated with chronic kidney disease and, especially, diabetic kidney damage by mechanisms to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent large-scale observational studies show that the uUMOD is an indicator of tubular health and could be used to identify individuals at higher risk of progressive kidney disease and mortality [26, 27]. Urate crystal nephropathies are common in patients with gout, with frequencies of 79–99% based on autopsy studies [10].…”
Section: Discussionmentioning
confidence: 99%
“…Independent of the well-known contribution of antidiuretic hormone to various forms of water disorders, recent epidemiological studies have shown significant associations between indices of the AVP/hydration system and the incidence or progression of diseases including chronic kidney disease (CKD), autosomal dominant polycystic kidney disease, diabetic nephropathy, obesity, metabolic syndrome, and insulin resistance [4,10,11,12,13,14,15,16,17,18,19,20,21]. A number of experimental studies have demonstrated the adverse effects of AVP or a low level of hydration in animal models of these disorders [10,22,23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%